ANTIBACTERIAL ACTIVITY OF ANDROGRAPHOLIDE ON THE GROWTH OF PORPHYROMONAS GINGIVALIS - Fauzia Nilam Orienty; Citra Lestari; Arieta Fadia Aunillah (Universitas Baiturrahmah, 2026)
Porphyromonas gingivalis is the main bacteria that causes periodontitis, and the use of antibiotics such as metronidazole can cause side effects and resistance. Andrographolide from the bitter plant is a natural alternative that has potential as an antibacterial. This study aims to evaluate the antibacterial activity of Andrographolide against P. gingivalis using the disc diffusion method at concentrations of 6 mg/mL, 8 mg/mL, and 10 mg/mL. Metronidazole 0.5 mg/mL was used as a positive control and 96% ethanol as a negative control. The results showed that Andrographolide concentrations of 6 mg/mL and 8 mg/mL produced a moderate inhibition zone, while a concentration of 10 mg/mL produced a strong inhibition zone. This study concluded that Andrographolide has antibacterial activity against P. gingivalis and shows an increase in inhibition with increasing concentration.